Multichannel marketing communications at retail enterprises - Liubov Lipych (Економічний форум)
The Russian war led to changes in trade policy and established marketing communications. The purpose of the article is to identify the essence of multichannel marketing communications of retail enterprises, new forms of interaction with target groups and consumers, and new sales models. It has been established that building relationships with all business participants in the retail trade system requires the development of relationship marketing. Relationship marketing is closely related to multi-channel trade, which consists in the simultaneous use and management of several sales channels by trading enterprises.It has been proven that the advantages of multi-channel trade are: attracting more customers, creating an opportunity to receive and collect information about them, as well as reducing costs for this activity. The disadvantages of multi-channel trade include: limited opportunities to use certain sales channels, the risk of "cannibalization" of specific sales channels, significant efforts associated with the process of synchronizing activities and the need for large investments. However, multi-channel commerce is becoming more common in retail. It is substantiated that the trading company tries to adapt its communication activities and communication messages to the needs of customers, who individually select information from a wide range of communication offers, independently determining the place of contact with the company - the so-called point of contact between customers and the company. There are direct and indirect and one-way and two-way contact points. In these points, the image of the company and/or its products is formed. Points of interaction with customers play a key role in the quality of relations with them. The rules for using multi-channel communication are highlighted. In the process of multi-channel communication, consumers should be perceived as equal partners, without a clear definition of the role of sender and receiver. The combination of push and pull communication strategies with their characteristic one-way and two-way communication and the corresponding tools should contribute to the creation of a synergy effect. Communication should be carried out both outside and "inside" the enterprise